Overcoming the crisis: Social and ecological impacts of the 17th and 18th century Northern Wars on Kazuń village (Poland) and its surrounding area - Związek, Tomasz; Obremska, Milena; Targowski, Michał; Sobechowicz, Łukasz; Siwek, Wojciech Aleksander; Gąsiorowski, Michał; Theuerkauf, Martin; Kozłowska-Szyc, Monika; Guzowski, Piotr; Poniat, Radosław; Mulczyk, Anna; Szewczyk, Krzysztof; et al. (Journal of historical geography, 2024)
The wars that ravaged the Polish–Lithuanian Commonwealth in the 17th century were among the most destructive events in the history of that part of Europe at the time. It is said that from this point on, the Polish–Lithuanian Commonwealth transitioned from a subject to an object state. Through interdisciplinary research involving the analysis of written, cartographic, and paleoecological data, we aim to demonstrate how the exit from this major crisis looked over a nearly 150-year perspective. In this article, we present observations describing economic, social, and demographic transformations, while also focusing on landscape and ecological issues. By analyzing the surroundings of the village of Kazuń (located today in central Poland), we highlight the emergence of a new type of settlement (the so-called olędrzy) in river valleys, which in the 18th century became an important element of a new wave of settlement and restoration. •Examines the transformation of the Medieval and Early Modern environment and landscape using various data.•Analyses the long-term social, economic and landscape changes that resulted from the wars occurred in the 17th and 18th centuries.•Discusses the transformation of the landscape in connection with the new wave of settlement during the 18th century.